Multi-wavelength autofluorescence characteristics and association with inflammation in acute posterior multifocal placoid pigment epitheliopathy: retina - Finger, Robert P.; Overbeck, Lennart J.; Berger, Moritz; Just, Marie D.; Koch, Jana K.; Terheyden, Jan H.; Foti, Selina; Schmid, Matthias; Holz, Frank G.; Ach, Thomas; Wintergerst, Maximilian W. M. (Investigative ophthalmology & visual science, 2025)
The purpose of this study was to investigate characteristics of chorioretinal lesions secondary to acute posterior multifocal placoid pigment epitheliopathy (APMPPE) using multi-wavelength fundus autofluorescence (FAF) and their association with intraocular inflammation. In this exploratory cross-sectional study, patients with chorioretinal lesions secondary to APMPPE underwent multimodal imaging including FAF with 450 nm, 488 nm, 518 nm, and 787 nm excitation wavelength, color fundus photography (CFP), and optical coherence tomography (OCT). Lesions were graded for FAF and CFP characteristics and inflammatory activity by an experienced image grader and an ophthalmologist. Association between these parameters was assessed using binary and ordinal regression models. Twenty-eight eyes (15 patients) with 597 lesions were included. Inter-reader reliability was almost perfect for qualitative image analysis and moderate for clinical activity grading. Lesions detectable on FAF were most often invisible (44.7%), followed by greyish/brownish in color (34.1%) on CFP. Invisible lesions on CFP were most frequently hypo-autofluorescent, whereas greyish/brownish colored lesions on CFP were most frequently hyper-autofluorescent on FAF. Ninety-nine percent of the lesions invisible on CFP were evident on 787 nm-excitation wavelength FAF (787 nm FAF). For multiple CFP categories, hyper- and iso-autofluorescence was more frequent on shorter wavelengths, and hypo-autofluorescence was more frequent on longer FAF excitation wavelengths. Hyper-autofluorescent lesions were more likely to be clinically active as compared to hypo-autofluorescent lesions (probabilities ranging between 0.85-0.87 and 0.51-0.61). FAF can aid phenotyping APMPPE lesions and assessing inflammatory activity and should therefore be routinely included in clinical management and studies. Especially 787 nm FAF allows visualization of APMPPE lesions not visible on clinical examination or CFP and could therefore be a valuable addition to routine imaging protocols.
Online veröffentlicht: 26. August 2025
Gesehen am 01.12.2025